2008
DOI: 10.1136/sti.2008.030049
|View full text |Cite
|
Sign up to set email alerts
|

Contraception to prevent HIV-positive births: current contribution and potential cost savings in PEPFAR countries

Abstract: Contraception is already having an important effect on reducing the number of infant HIV infections. This contribution could be strengthened by additional efforts to provide contraception to HIV-infected women who do not wish to become pregnant. Moreover, the effect of contraception can be achieved at a cost savings compared with PMTCT services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
114
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 20 publications
3
114
1
Order By: Relevance
“…However, we did account for the reduction of unintended pregnancies in HIV-infected women owing to the provision of oral contraception for 2 years postpartum. [27][28][29] Second, because we restricted costing methods to operating costs only, our estimates cannot be easily compared with values from the few relevant studies that have included capital costs. Third, to estimate national costs we multiplied unit costs by the reported numbers of individuals using particular PMTCT services in each country.…”
Section: Discussionmentioning
confidence: 95%
“…However, we did account for the reduction of unintended pregnancies in HIV-infected women owing to the provision of oral contraception for 2 years postpartum. [27][28][29] Second, because we restricted costing methods to operating costs only, our estimates cannot be easily compared with values from the few relevant studies that have included capital costs. Third, to estimate national costs we multiplied unit costs by the reported numbers of individuals using particular PMTCT services in each country.…”
Section: Discussionmentioning
confidence: 95%
“…Globally, contraceptive use and its agreement is related to the range of methods available, patient choice, prevalent health and religious beliefs, perceptions of method effectiveness, and side effects 21 . Despite the fact that the contributions of contraception to reducing mother to child transmission (MTCT) have been well documented [22][23][24] . But, it is observed that the contraceptive prevalence rate is the lowest (mean = 29.66) in the highest HIV prevalence region (mean = 5.01), Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Effective contraceptive utilization could prevent unintended pregnancies among HIV/AIDS patient. In fact, the effectiveness of contraceptive use in preventing HIV positive births has already been established [14].…”
Section: Introductionmentioning
confidence: 99%